1995
DOI: 10.1017/s135772980001359x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime productivity in gilts previously selected for decreased age at puberty

Abstract: A study was conducted to evaluate the effect of decreasing age of puberty on lifetime productivity in sows. Two lines of gilts from the Nebraska Gene Pool population were used in this study: a line that had been selected for decreased age at puberty (AP) and a line in which selection had been random (RS). The study was conducted in two parts. In part one, 75 gilts were mated at second oestrus and the productivity measured over five parities. A second experiment utilizing 68 gilts was conducted to provide furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Puberty induction at an early age (135-140 days of age) serves to identify the early responders and likely more fertile gilts during their breeding lifetime, since gilts selected for decreased age at puberty resulted in a higher percentage of sows farrowing after five parities (Holder et al, 1995). Patterson et al (2003) reported that out of 508 gilts stimulated with daily boar contact from 140 days of age, 75% of gilts were pubertal within 40 days of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Puberty induction at an early age (135-140 days of age) serves to identify the early responders and likely more fertile gilts during their breeding lifetime, since gilts selected for decreased age at puberty resulted in a higher percentage of sows farrowing after five parities (Holder et al, 1995). Patterson et al (2003) reported that out of 508 gilts stimulated with daily boar contact from 140 days of age, 75% of gilts were pubertal within 40 days of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not examine the association of early puberty with sow longevity, but other researchers have suggested that selection of gilts for reduced age at puberty improved their reproductive performance by increasing the proportion of animals retained in the herd through the first three parities (Patterson et al 2010) or the first six parities (Flowers 2011) and increased the average parity of culled sows at removal (Holder et al 1995). This should be an additional consideration in evaluating gilt selection programs.…”
Section: Discussionmentioning
confidence: 84%
“…) or the first six parities (Flowers ) and increased the average parity of culled sows at removal (Holder et al. ). This should be an additional consideration in evaluating gilt selection programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations